Black and White Patients With Staphylococcus aureus Bacteremia Have Similar Outcomes but Different Risk Factors. (14th November 2022) - Ruffin, Felicia; Dagher, Michael; Park, Lawrence P; Wanda, Lisa; Hill-Rorie, Jonathan; Mohnasky, Michael; Marshall, Julia; Souli, Maria; Lantos, Paul; Sharma-Kuinkel, Batu K; Maskarinec, Stacey A; Eichenberger, Emily M; et al.
Abstract: Background: Staphylococcus aureus bacteremia (SAB) disproportionately affects Black patients. The reasons for this disparity are unclear. Methods: We evaluated a prospectively ascertained cohort of patients with SAB from 1995 to 2020. Clinical characteristics, bacterial genotypes, and outcome were compared among Black and White patients with SAB. Multivariable logistic regression models were used to determine factors independently associated with the outcomes. Results: Among 3068 patients with SAB, 1107 (36%) were Black. Black patients were younger (median, 56 years vs 63 years; P < .001) and had higher rates of diabetes (47.5% vs 34.5%, P < .001), hemodialysis dependence (40.0% vs 7.3%, P < .001), and human immunodeficiency virus (6.4% vs 0.6%, P < .001). Black patients had higher rates of methicillin-resistant S. aureus (49.3% vs 44.9%, P = .020), including the USA300 hypervirulent clone (11.5% vs 8.4%, P = .007). White patients had higher rates of corticosteroid use (22.4% vs 15.8%, P < .0001) and surgery in the preceding 30 days (28.1% vs 18.7%, P < .001). Although the median Acute Physiology Score (APS) at the time of initial SAB diagnosis was significantly higher in Black patients (median APS, 9; interquartile range [IQR], 5–14 vs median APS, 7; IQR, 4–12; P < .001), race was not associated with 90-day mortality (risk ratio, 1.02; 95% confidence interval, .93–1.12), and rates of metastatic infection were lower among Black patients (37.2% vs 41.3% White, P = .029). Conclusions: Despite differences in Black patients' higher APS on presentation and more risk factors, including a 5 times higher risk of hemodialysis dependence, 90-day mortality among Black and White patients with SAB was similar. Abstract : Among a prospectively enrolled cohort of patients with Staphylococcus aureus bacteremia, Black and White patients had similar outcomes despite significant differences in risk factors.